TINDAK TUTUR PERMINTAAN MAAF PADA GERAKAN OJIGI (ãŠè¾žå„€) DALAM FILM SHAZAI NO OUSAMA - Novridawati, Jenny; Isnaini, Zuli Laili; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to describe the type of speech act of apology in motion ojigi (ãŠ è¾ž å„€) with sociolinguistic approaches and to describe the situation by ningen kankei (human relationships). This study subject is film Shazai no Ousama by Nobuo Mizuta on 2013. The study used descriptive qualitatif approach and analyzed by Dell Hymesâ€Ÿs â€œSPEAKINGâ€ theory and Kabayaâ€Ÿs â€œNingen Kankeiâ€ theory. As the result we discovered that there are some various apologies with various politness level that has been used in dayly life. The level of polite is use in the speech apology with movement ojigi a have relevance to the situation and ningen kankei between speakers. There are 8 speech act of apology to the movement ojigi that is: moushiwake arimasen (saikeirei), sumimasen deshita (saikeirei), shitsurei shimashita (saikeirei), moushiwake arimasen (keirei), moushiwake gozaimasu deshita (saikeirei), moushiwake arimasu (eshaku), gomen (eshaku), dan sumimasen (eshaku).Keywords: speech act, apology, ojigi.